2020
DOI: 10.3144/expresspolymlett.2020.6
|View full text |Cite
|
Sign up to set email alerts
|

Poly(N-isopropylacrylamide-co-N-vinylpyrrolidone) thermoresponsive microspheres: The low drug loading ensures the pulsatile release mechanism

Abstract: Poly(N-isopropylacrylamide-coN -vinylpyrrolidone) (poly(NIPAAm-co-NVP)) with a co-monomer molar ratio in copolymer of 91.5/8.5 (NIPAAm/NVP) was synthesized as an interesting thermosensitive material possessing a sharp phase transition at 36°C under simulated physiological conditions. The effect of the co-monomer molar ratio as well as of the ionic strength and nature of ions on the lower critical solution temperature (LCST) was investigated. Cross-linked poly(NIPAAm-co-NVP) thermoresponsive microspheres were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…2h). 78 The adjustable LCST behaviour of the derivatives of PNIPAM and copolymers indicated that it is highly promising to be applied in biomedical field, because the transition temperature can be tuned. This might be relevant for different tissue environments.…”
Section: Poly(n-isopropylacrylamide) Its Co-polymers and Derivativesmentioning
confidence: 99%
“…2h). 78 The adjustable LCST behaviour of the derivatives of PNIPAM and copolymers indicated that it is highly promising to be applied in biomedical field, because the transition temperature can be tuned. This might be relevant for different tissue environments.…”
Section: Poly(n-isopropylacrylamide) Its Co-polymers and Derivativesmentioning
confidence: 99%
“…Finally, the microspheres were loaded with a model drug—diclofenac. The release of that drug through the pulsatile mechanism was investigated [ 96 ]. In another try, a new microgel based on acrylamide (AAM), 1-vinyl-2-pyrrolidone (NVP), and 2-(diethylamino)ethyl methacrylate (DEAEMA) was prepared.…”
Section: Pvp In Micro- and Nano Drug Delivery Systemsmentioning
confidence: 99%
“…( b ) LCST profiles of poly(NIPAAm- co -NVP) nanoparticles under simulated physiological conditions showing influence of pVP on LCST of polymers. Reproduced with permission from [ 96 ], Budapest University of Technology and Economics, 2019 ( c ) TEM images of pVP functionalized gold nanoparticles with curcumin and scheme of possible conjugation of Cur with pVP coated Au-Nps. Reproduced with permission from [ 62 ], Elsevier, 2012.…”
Section: Figurementioning
confidence: 99%
“…Interesting results can be obtained when choosing comonomers of a more different chemical nature. For example, the copolymerization of NIPAAm with N-vinylpyrrolidone (NVP) in a 91.5:8.5 ratio affords thermoresponsive systems with an LCST value of 36 • C in simulated physiological conditions [46]. Because the two comonomers have weak ionizable units, the LCST is sensible to the surrounding ionic strength and pH, higher LCST values (37.3 • C) being obtained in a simulated gastric fluid environment (pH 1.2).…”
Section: Introductionmentioning
confidence: 99%